Pengaruh Return On Asset, Sales Growth, Asset Growth, Cash Flow, Dan Likuiditas Terhadap Dividend Payout Ratio Perusahaan Perbankan Di Bursa Efek Indonesia Tahun 2009 - 2013 - Poernawarman -; Kamaliah -; Nur Azlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the effect of ROA on Dividend Payout Ratio on Banking Companies Listed in Indonesia Stock Exchange, to determine the effect of the Sales Growth Dividend Payout Ratio on Banking Companies Listed in Indonesia Stock Exchange, to determine the effect of the Asset Growth Dividend Payout Ratio on Banking company Listed in Indonesia Stock Exchange, to determine the effect of the Cash Flow Dividend Payout Ratio on Banking Companies Listed in Indonesia Stock Exchange, to determine the effect of the Dividend Payout Ratio Liquidity in Banking Companies Listed in Indonesia Stock Exchange, to determine the effect of ROA , Sales Growth, Asset Growth, Cash Flow and Liquidity together against Dividend Payout Ratio on Banking Companies listed on the Indonesia Stock Exchange. The population in this study are all companies belonging to banking in Indonesia Stock Exchange (IDX). In accordance with the IDX publication shows that the number of listed companies in the period 2009-2013 a number of 45 issuers. In this study, the selected sample is 15 banking company incorporated in a row during 2009-2013 in Indonesia Stock Exchange. Analysis of the data used to test for normality, classic assumption test, F test, t test and the coefficient of determination. The results showed a significant effect on the Return On Parliament on Commercial Banks in IDX. Thus, Hypothesis 1. The results showed that SG significant effect on the House on Commercial Banks in IDX. Thus, Hypothesis 2 is acceptable. The results showed that AG significantly influence the House on Commercial Banks in IDX. Thus, Hypothesis 3 is acceptable. The results showed that the CF significantly influence the House on Commercial Banks in IDX. Thus, Hypothesis 4 is acceptable. The results showed that CR significantly influence the House on Commercial Banks in IDX. Thus, Hypothesis 5 is acceptable. From the test results simultaneously known that the independent variables simultaneously have a significant influence on the House of Commercial Banks companies in IDX.Keywords: Return on Assets, Sales Growth, Asset Growth, Cash Flow, Liquidity and Dividend Payout Ratio.